Study on sedimentary organic facies of coal-measure source rocks in Shuixigou Group, Taibei Sag, Tuha Basin - Hao LIANG; Tanguang FAN; Zhiyong WANG; Shu TAO; Yijie WEN; Haitian ZHENG; Zijian ZHANG (Shiyou shiyan dizhi)
The Taibei Sag in the Tuha Basin contains abundant oil and gas resources. The coal-measure source rocks in the Jurassic Shuixigou Group are the main hydrocarbon source layers in the area, with significant hydrocarbon generation potential. However, organic facies types of the coal-measure source rocks in the Shuixigou Group and their relationships with sedimentary environments remain unclear, hindering oil and gas exploration across the sag and the entire basin. To enable a detailed classification and evaluation of coal-measure source rocks in the Shuixigou Group of the Tuha Basin, geochemical analyses were conducted, including maceral composition, total organic carbon (TOC) content, and hydrocarbon generation potential (S1+S2). Based on the result, the study established classification criteria for sedimentary organic facies of coal-measure source rocks in the study area, identified organic facies types, and clarified hydrocarbon generation potential and their relationships with sedimentary facies. The results indicate that the sedimentary organic facies of the coal-measure source rocks in the Shuixigou Group of the Taibei Sag can be categorized into five types: organic facies of lacustrine with strong water coverage and high vitrinites, organic facies of lacustrine with water coverage and medium to high vitrinites, organic facies of delta plain with water coverage and medium to high vitrinites, organic facies of delta plain with weak water coverage and medium vitrinites, and organic facies of front delta with weak water coverage and low vitrinites. The organic facies of lacustrine with strong water coverage and high vitrinites have a large organic abundance and exhibit the highest hydrocarbon potential, with TOC contents ranging from 5.05 % to 18.31 % and S1+S2 values from 6.35 to 20.93 mg/g, and vitrinites exceeding 80%. Following this, the organic facies of lacustrine with water coverage and medium to high vitrinites and the organic facies of delta plain with water coverage and medium to high vitrinites exhibit TOC contents of 3.83%-17.68% and 2.30%-7.41%, with average S1+S2 values of 6.35 mg/g and 4.48 mg/g, and vitrinites ranging between 50%-80%, respectively. The organic facies of front delta with weak water coverage and low vitrinites show the poorest hydrocarbon generation potential, with an average TOC content of only 1.3% and an average S1+S2 of 4.1 mg/g. The findings provide a critical basis for predicting the distribution of coal-measure high-quality source rocks in the Shuixigou Group in the Taibei Sag and for accurately assessing their oil and gas resource potential.